Optimizing Regional Original Income: A Comprehensive Analysis and Assessment of Revenue Management Practices in Pangkajene Regency and Islands - Nur Sandi Marsuni; Nur Asmi Ainun kamal (Pustaka Digital Indonesia, 2024)
This research delves into the optimization of regional original income and scrutinizes its recording practices in Pangkajene Regency and Islands for the years 2021-2022. Employing a descriptive qualitative research method, data was collected through observation, interviews, and documentation. The findings reveal that the regional original income in Pangkajene and Islands comprises various taxes including hotel tax, restaurant tax, entertainment tax, advertising tax, street lighting tax, parking tax, underground water tax, class C mineral tax, land and building tax, and BPHTB tax. Despite an increase in tax realization from IDR 90,323,492,905.46 in 2021 to IDR 90,906,902,478.70 in 2022, both years failed to meet the set targets. The Covid-19 pandemic has profoundly impacted both national and regional economies, leading to a decline in state revenues and consequently affecting regional revenues. Amidst reduced transfer funds and relaxations in revenue targets, local governments face challenges in achieving local original income targets. Fiscal decentralization grants regions autonomy in managing their own affairs, with local original income serving as a crucial revenue source. However, fluctuating economic conditions, exacerbated by the pandemic, influence the realization of regional income targets. Analyzing the data, it becomes evident that certain types of taxes exhibited varying performance between 2021 and 2022, emphasizing the need for dynamic strategies in regional revenue management. The study underscores the importance of enhancing supervision and control mechanisms to stabilize revenue fluctuations and improve contributions to regional development. Additionally, optimizing local revenue sources is recommended to mitigate large annual fluctuations. This research contributes to understanding revenue management practices and informs policymakers on strategies to bolster regional income amid economic uncertainties.